Oral Lichen Planus: Clinical Features, Etiology, Treatment and Management; A Review of Literature - Marzieh Boorghani; Narges Gholizadeh; Ali Taghavi Zenouz; Mehdi Vatankhah; Masoumeh Mehdipour (Tabriz University of Medical Sciences, 2010)
Lichen planus is a chronic inflammatory mucocutaneous disease. Mucosal lesions are classified into six clinical forms and there is malignant potential for two forms of OLP; therefore, follow-up should be considered. There are many unestablished etiological factors for OLP and some different treatment modalities are based on etiology. The aims of current OLP therapy are to eliminate mucosal erythema and ulceration, alleviate symptoms and reduce the risk of oral cancer. We have used review papers, case reports, cohort studies, and case-and-control studies published from 1985 to 2010 to prepare this review of literature.